VEGETABLE AND CUCURBITS CROPS. RESULTS OF INVESTIGATION IN 2012 - I. V. Savchenko; N. I. Bocharnikova (Овощи России, 2012)
The short results of investigation in 2012 of the Institutes of Russian Academy of Agricultural Science, Russian Academy of Science, and Institutions of Higher Education in the field of development of new varieties and high-precision and environmentally safe technologies of zonal agriculture of vegetable and cucurbits crops with utilization of new cultivars and hybrids, high-quality seeds, modern types of growing and mechanical equipment are described in the article.